SAC INTERACTIVE LEARNING MEDIA FOR IMPROVING LEARNING OUTCOMES BUILDING IDENTITY IN DIVERSITY FOURTH-GRADE STUDENTS - Nuraida; Deny Setiawan; Yusnadi (Universitas Majalengka, 2025)
This study was motivated by the low learning outcomes of students in Pancasila education due to the lack of innovation in the learning process. Therefore, this study aims to develop interactive SAC learning media on the subject of building identity in diversity to improve the learning outcomes of fourth-grade elementary school students. This study is a 4D model Research and Development applied at SDN 057224 Paluh Gusta. The data used came from questionnaires for experts on material, media and language for feasibility, questionnaires on practicality from teachers, and tests for student learning outcomes. The results showed that the interactive SAC media for building identity in diversity had a material expert feasibility rating of 90%, classified as ‘Very Good’, a media expert rating of 92%, classified as ‘Very Good’ and 91% classified as ‘Very Good’ for language experts, while the level of practicality obtained was 93% classified as ‘Very Practical’. Student learning outcomes improved from a pre-test score of 65 to a post-test score of 90, and the gain test result was 0.714, which is ‘Very High’. Therefore, the interactive learning media SAC material on building identity in diversity that was developed is appropriate and valid and is able to improve student learning outcomes. Applying this interactive learning media SAC in the learning process in the classroom will make the learning atmosphere even better and more effective, and this study contributes greatly to the development of technology in education today.